1991
DOI: 10.3354/meps078241
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium regeneration in the Scotia-Weddell Confluence area during spring 1988

Abstract: The presence of laige ammonium stocks and the related enhanced quant~ties of microheterotrophs in the Scotla-Weddell Confluence area lndicate the importance of ammonium i e m~n e r alization processes there Maximal ammonium concentrations in the marglnal ice zone amounted to Inore than 2 pm01 N 1.' and ren~lneralization rates in this zone were consistently hlgher than those measured In the adjacent open ocean and permanently ice-covered zones At one statlon, characterized by a large knll swarm, the remlnerallz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The actual mechanism by which krill is implicated in NH 4 + regeneration may not be direct or obvious (Whitehouse et al 2011), and it has been suggested that krill excretion may enhance bacterial activity (Goeyens et al 1991;Aristegui et al 2014), fuelling phytoplankton growth, and thus stimulating periods of high productivity in the Southern Ocean (Smetacek 2008;Aristegui et al 2014). However, the direct excretion of dissolved ammonium can also be the primary boost to mixed layer NH 4 concentrations (Whitehouse et al 2011;Lehette et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual mechanism by which krill is implicated in NH 4 + regeneration may not be direct or obvious (Whitehouse et al 2011), and it has been suggested that krill excretion may enhance bacterial activity (Goeyens et al 1991;Aristegui et al 2014), fuelling phytoplankton growth, and thus stimulating periods of high productivity in the Southern Ocean (Smetacek 2008;Aristegui et al 2014). However, the direct excretion of dissolved ammonium can also be the primary boost to mixed layer NH 4 concentrations (Whitehouse et al 2011;Lehette et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This form of reduced nitrogen in Antarctic waters can be obtained from several sources: sea ice, that usually represents a source of reduced organic and inorganic nitrogen during the melting season (e.g., Brandini and Bauman 1997), microbial regeneration (Goeyens et al 1991), and, in some coastal areas, terrestrial sources from bird and mammal colonies (Tatur and Myrcha 1983). Amongst ammonia sources, zooplankton recycling of nutrients also plays an important role, conditioning the pelagic ecosystem in the Southern Ocean to maintain it at a high productivity level (Alcaraz et al 1998;Lehette et al 2012;Arístegui et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Goeyens et al [33] reported an extremely high bacterial activity and almost negligible protozoan grazing after the recent passage of a krill swarm, at one station in the Scotia-Weddell Confluence Area. While feeding on bacterial grazers, krill release large amounts of organic (DOM) and inorganic (ammonium, phoshate, iron, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…N regeneration processes were capable of completely replacing the DIN pool within 1 d at both depths and all provinces examined within the (Raimbault et al 1999) ,100 5-20 Mediterranean Sea-coastal region (Selmer et al 1993) 60-270 120-960 Mediterranean Sea-coastal region (Diaz and Raimbault 2000) 10-230 50-220 Western English Channel coastal region (Maguer et al 1999) 120-500 0-648 Western English Channel coastal region (Le Corre et al 1996) 50-700 0-664 Sargasso Sea (Glibert 1982) 0-400 9-2,088 Arabian Sea (McCarthy et al 1999) 0-400 240-1,800 Southern Ocean-permanently open ocean zone (Goeyens et al 1991) 100 The determination of N assimilation rates using 15-N methods assumes a constant enrichment of the substrate pool for the duration of the incubation (Dugdale and Goering 1967). Earlier studies acknowledged that in vitro NH z 4 regeneration invalidated this assumption, leading to an emphasis on simultaneous N assimilation and NH z 4 regeneration rate determinations (Glibert et al 1982;Sambrotto 2001).…”
Section: Discussionmentioning
confidence: 99%